2021
DOI: 10.1002/mabi.202000396
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mechanically Strong Nondegradable Protein Hydrogel with a Sponge‐Like Morphology

Abstract: Protein‐based hydrogels are important functional materials with many potential applications. However, the relatively small pore size and poor mechanical properties substantially limit their application. Here a superporous bovine serum albumin (BSA) hydrogel is prepared with high porosity and interconnectivity by using BSA and 1,2,7,8‐diepoxyoctane (DEO). The equilibrium water contents of hydrogels can reach 76.5%. Moreover, the BSA hydrogels show excellent mechanical properties and excellent deformation recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…[30] Therefore, tremendous improvements have been made to fabricate structured macro-porous hydrogels for facilitating mass transport, cell encapsulation, and thereafter tissue ingrowth through various methods, such as emulsion-templating technique, [31] aqueous dynamic phase separation, [32,33] in situ gas formation, [34,35] enzymatic or ionic crosslinking of microgels, [36,37] cryogelation based on frozenthawing cycles, [38] combination of thermal denaturation and chemical crosslinking. [39] However, most studies claiming macro-porous sizes (>100 μm) in hydrogels were observed in the dry state typically following lyophilization of a frozen sample, which did not depict the original porosity of the gel but rather the architectures associated with ice crystal formation during the frozen-dry treatment. The original pore size and porosity of the as-prepared hydrogels were far smaller than that of their dry state, which are still less than satisfactory compared to that of waterless polymer scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Therefore, tremendous improvements have been made to fabricate structured macro-porous hydrogels for facilitating mass transport, cell encapsulation, and thereafter tissue ingrowth through various methods, such as emulsion-templating technique, [31] aqueous dynamic phase separation, [32,33] in situ gas formation, [34,35] enzymatic or ionic crosslinking of microgels, [36,37] cryogelation based on frozenthawing cycles, [38] combination of thermal denaturation and chemical crosslinking. [39] However, most studies claiming macro-porous sizes (>100 μm) in hydrogels were observed in the dry state typically following lyophilization of a frozen sample, which did not depict the original porosity of the gel but rather the architectures associated with ice crystal formation during the frozen-dry treatment. The original pore size and porosity of the as-prepared hydrogels were far smaller than that of their dry state, which are still less than satisfactory compared to that of waterless polymer scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine serum albumin (BSA), a biocompatible natural protein, has great hemostatic potential due to its hydrophilicity, but its weak mechanical qualities restrict its applicability. Wang et al 80 added the inorganic salt NaCl to BSA to facilitate the gelation process by shielding the electrostatic repulsion between BSA molecules, resulting in the better water-holding capacity of the hydrogel. This BSA-based hydrogel's equilibrium swelling water content reached 76%.…”
Section: Increasing the Concentration Of Localized Hemostatic Substancesmentioning
confidence: 99%
“…Different biomaterial forms of SA and potential applications in bone regeneration. Reproduced with permission from refs . Copyright 2018 American Chemical Society, Copyright 2021 Qiu, X. et al, Copyright 2021 Wiley-VCH, Copyright 2021 Elsevier, and Copyright 2008 American Chemical Society, respectively.…”
Section: Morphological Diversification Of Sa-derived Biomaterials For...mentioning
confidence: 99%